Staphylococcal Pericarditis Causing Pericardial Tamponade and Concurrent Empyema. (18th July 2019) - Kondapi, Divya; Markabawi, Danny; Chu, Andrew; Gambhir, Harvir Singh
Abstract : Bacterial pericarditis is a rare presentation and is usually due to secondary infection from a hematogenous cause or can occur secondary to trauma, intrathoracic surgery, or due to spread of infection from a contiguous focus via ligaments that anchor the pericardium to its surrounding structures. Its course is fulminant characterized by a high mortality rate from sepsis, tamponade, and constriction. We describe a rare case of Staphylococcus aureus pericarditis with concurrent unilateral empyema. The patient rapidly developed tamponade and was successfully treated with antibiotics and urgent percutaneous pericardial drainage with placement of a temporary catheter. Treatment for bacterial pericarditis typically is 4–6 weeks long. Thoracic surgery should be consulted as soon as possible to determine need for surgical intervention, as fibrin deposition may occur, making percutaneous drainage incomplete and leading to complications of persistent purulent pericarditis or constrictive pericarditis.